Tetraalkylammonium derivatives as real-time PCR enhancers and stabilizers of the qPCR mixtures containing SYBR Green I - Shaik, Gouse M; Dráberová, Lubica; Dráber, Peter; Boubelík, Michael; Dráber, Petr (Nucleic acids research, 2008)
Tetraalkylammonium (TAA) derivatives have been reported to serve as stabilizers of asymmetrical cyanine dyes in aqueous solutions and to increase the yield and efficiency of polymerase chain reaction (PCR) detected by end-point analysis. In this study, we compared the ability of various TAA derivatives (with alkyl chain ranging from 1 to 5 carbons) and some other compounds to serve as enhancers of real-time PCR based on fluorescence detection from intercalating dye SYBR Green I (SGI). Our data indicate that TAA chlorides and some other TAA derivatives serve as potent enhancers of SGI-monitored real-time PCR. Optimal results were obtained with 10-16 mM tetrapropylammonium chloride. The effect of TAA compounds was dependent on the nature of counter ions present and composition of the reaction mixtures used. Based on measurements of SGI-generated fluorescence signal in the presence of PCR-amplified DNA fragments, oligonucleotide primers and/or various additives, we propose that TAA-derivatives reduce the binding of SGI to oligonucleotide primers and thus enhance primer-template interactions during annealing phase. Furthermore, these compounds serve as stabilizers of SGI-containing PCR mixtures. The combined data indicate that TAA derivatives might be a new class of additives contributing to robustness of real-time PCR monitored by asymmetrical cyanine dye SGI.
Keywords: fluorescenční barviva; Quaternary Ammonium Compounds; Financing, Organized; zvířata; Organic Chemicals; Polymerase Chain Reaction; Fluorescent Dyes; myši inbrední C57BL; Mice; Temperature; Mice, Inbred C57BL; myši; teplota; financování organizované; Animals; kvartérní amoniové sloučeniny; organické látky; polymerázová řetězová reakce